Mahalle Yönetimi ve Temel Sorunları - Karakaya, Sedat (My University, 2020)
Yerel yönetim alanında yapılanmevzuat değişiklikleri göz ününe alındığındamahalle yönetimleri, merkez ve yerel arasındakalan bir yer teşkil etmektedir. Mahalleyönetimleri konusunda herhangi bir değişikliğinyapılmamış olması, mahallelerin anakronik birmesele olarak kalmasına neden olmuştur. Yerelyönetim mevzuatlarında birçok değişiklikyapılmasına rağmen yerel demokrasininbe şiğini t e şkil eden köy ve maha ll eyönetimlerine bigane kalınması kentselalanların temelini teşkil eden mahalleyönetimlerini birçok sorunla karşı karşıyabırakmıştır. Diğer yerel yönetim birimleridevingen bir mevzuat değişikliğine tabiiolurken, yerel demokrasinin ilk sacayağınıteşkil eden bu birimler 65 yılı aşan kanunlarlayönetilmektedirler. Birçok benzerliğe karşınmahalle yönetiminin sahip olduğu sorunlar onuköy yönetiminden ayırarak sahip olduğuproblemleri sistematik hale getirmektedir. Buamaçla çalışmada; Osmanlıdan Cumhuriyeteintikal eden tarihsel misyonuyla mahalleyönetiminin gelişimi ve Cumhuriyet dönemindeyaşadığı mevzuat değişikliklerinin yanı sıra,“kimlik sorunu” başta olmak üzere, “nüfus” veyeni büyükşehir mevzuatı çerçevesindekisorunları ele alınmıştır. Mahalle yönetimininbizce en önemli sorunu olarak görülen busorunlar, mahalle yönetimlerini birçoktartışmanın odağına taşımış bulunmaktadır. Buhedefle mahalle yönetimlerine ilişkin birtakımöneriler tartışılmıştır

Given the legislative changes made in the local administration area, it is seen that the neighborhood administrations remain between the center and the local. The fact that no changes have been made regarding neighborhood administrations caused the neighborhoods to turn into an anachronical problem. Although many changes have been made in local government regulations, the lack of interest in the village and neighborhood administrations that form the basis of local democracy has left the neighborhood administrations that constitute the basis of the urban areas facing many problems. While other local government units are subject to dynamic legislation neighborhood governments, which constitute the first pillar of local democracy, are governed by laws over 65 years. Despite many similarities, the problems of the neighborhood administration make it systematic by separating it from the village administration. In this study, firstly, the development of neighborhood management is discussed with its historical mission from the Ottoman to the Republic. In addition to the legislative changes made in the Republican period, the problems within the framework of "population" and the new metropolitan legislation, especially the "identity problem", have been discussed. These topics, which constitute the main problems of neighborhood management, have been examined in detail and some solutions for these problems have been presented.
Neighborhood Governance and it's Main Problems